THE EFFECT OF INTRODUCTORY VIDEOS IN YOUTUBE ON STUDENTS’ ACHIEVEMENT IN SPEAKING SKILL OF THE TENTH GRADE - Linda Lestari; Iskandar Zulkarnain; Syafrina Prihatini (English Education Study Program FKIP Universitas Alwashliyah Medan, 2022)
The purpose of this research was to find out whether introductory videos in YouTube have effect on students’ speaking skill. The research was conducted using experimental research design. The population was the students of grade X at SMKS Muhammad Yaasiin Sei Lepan. The sampling technique used was cluster random sampling. X TKJ 1 was selected as experimental group and X TKJ 2 was selected as control group. Each class consisted of 26 students and the total sample was 52 students. Research instrument to collect the data was speaking test with the criteria of pronunciation, fluency, accuracy, and vocabulary. During the treatment, experimental group was taught using introductory videos in YouTube while control group was taught descriptively. The data obtained namely mean score of post-test in experimental group was 83.46 while 55.0 were the mean score of post-test in control group. Both groups mean score were analyzed using t-test formula. It showed that t-observed value was 11.05 and t-table value was 2.008 with df=50. By comparing both value, it was known that t-observed was higher than t-table (11.5>2.008). Therefore, the alternative hypothesis (Ha) was accepted. The research concluded that introductory videos in YouTube significantly affected the students’ speaking skill.